Alternating electric-field-induced assembly of binary mixtures of soft repulsive ionic microgel colloids - Jathavedan, Kiran; Bhat, Suresh K.; Mohanty, Priti S. (Journal of Colloid and Interface Science, 2019)
An external alternating electric field is used to study the assembly of a binary mixture of Poly(N-isopro pylacrylamide-co-acrylic acid) microgels in their swollen form at hydrodynamic size ratio 2:1 under deprotonated state. The AC field experiments were carried out at a fixed frequency of 100 kHz in the fluid regime for three number density ratios 1:3, 1:1 and 3:1 of big-to-small microgels using a confocal microscope. Strings with different types of co-assembly structures such as buckled, ring, flame and sandwich have been observed at low and intermediate field strengths at ratio 1:3, 1:1. In buckled and ring type, one or two small particles sit at the contact of two big particles and in the flame type, small particles arrange like a cone at end of the string. In the sandwich structure, several double small particle layers lie in between big particles. At high field strength, aggregation of strings and a phase separation into individual aggregates of strings from both big and small microgels have been observed. At higher ratio 3:1, the string formation is mostly dominated by big particles. Our experimental results are discussed with the recent simulation and experimental works on AC field induced structures in binary hard sphere mixtures. (C) 2019 Elsevier Inc. All rights reserved.
Keywords: assembly; dipolar interactions; Microgels; Soft colloids

Active site engineering and theoretical aspects of ``Superhydrophilic'' nanostructure array enabling efficient overall water electrolysis - Barik, Sidharth; Kharabe, Geeta Pandurang; Illathvalappil, Rajith; Singh, Chandrodai Pratap; Kanheerampockil, Fayis; Walko, Priyanka S.; Bhat, Suresh K.; Devi, R. Nandini; Vinod, C. P.; Krishnamurty, Sailaja; Kurungot, Sreekumar (Small, 2023)
The rational design of noble metal-free electrocatalysts holds great promise for cost-effective green hydrogen generation through water electrolysis. In this context, here, the development of a superhydrophilic bifunctional electrocatalyst that facilitates both oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) in alkaline conditions is demonstrated. This is achieved through the in situ growth of hierarchical NiMoO4@CoMoO4 center dot xH(2)O nanostructure on nickel foam (NF) via a two-step hydrothermal synthesis method. NiMoO4@CoMoO4 center dot xH(2)O/NF facilitates OER and HER at the overpotentials of 180 and 220 mV, respectively, at the current density of 10 mA cm(-2). The NiMoO4@CoMoO4 center dot xH(2)O/NF parallel to NiMoO4@CoMoO4 center dot xH(2)O/NF cell can be operated at a potential of 1.60 V compared to 1.63 V displayed by the system based on the Pt/C@NF parallel to RuO2@NF standard electrode pair configuration at 10 mA cm(-2) for overall water splitting. The density functional theory calculations for the OER process elucidate that the lowest Delta G of NiMoO4@CoMoO4 compared to both Ni and NiMoO4 is due to the presence of Co in the OER catalytic site and its synergistic interaction with NiMoO4. The preparative strategy and mechanistic understanding make the windows open for the large-scale production of the robust and less expensive electrode material for the overall water electrolysis.
Keywords: density functional theory (DFT) study; hydrogen evolution reaction (HER); Hydrothermal synthesis; oxygen evolution reaction (OER); superhydrophilic nanostructures; synergistic interaction; water electrolysis